Cooperación y conflicto en la Agenda 2030: ¿una relación desequilibrada? - Guillermo Santander-Campos (Revista Iberoamericana de Estudios de Desarrollo)
Among the virtues of the 2030 Agenda is that of trying to provide a more comprehensive and urgent response to the challenges raised by an increasingly complex and changing world. This purpose has led to putting the cooperative dimension at the centre of the agenda understanding that, in a globalized and interdependent world, it will be impossible to address the challenges posed if it is not by articulating different forms of concerted responses. However, although this cooperative dimension is unavoidable to achieve the goals set, achieving this agenda also seems to require progress in a more conflictive dimension, that has occupied a residual space to date. This article addresses this issue, analysing some key areas in which it will be necessary to assume conflicting logics and the political and institutional implications that should derive from it in the future.